Esquiva e fuga: diálogos entre Heidegger e o Buda acerca do modo de ser na cotidianidade - Wruck, Jeferson (2024)
This dissertation proposes a dialogue between Martin Heidegger and the Buddha on the mode of being in everyday life, exploring convergences and differences in their perspectives on existence. For Heidegger, everydayness is the most common mode of existence, characterized by routines, habits, and conventions that obscure our relationship with the essence of existence. Similarly, the Buddha describes samsaric existence as a cycle of conditioned behaviors and beliefs that trap the mind in patterns of attachment and ignorance. Both suggest that this ordinary way of life diverts attention from the true nature of being: interdependent, impermanent, and without fixed essence. In the first part of the work, we analyze each author individually. Heidegger, in the first chapter, is presented through his existential analytic in Being and Time, with a focus on concepts such as being-in-the-world, understanding, state-of-mind and discourse. The Buddha's thought is explored in the second chapter with an emphasis on the notions of non-self, impermanence, and suffering. In the second part, chapters three and four, we confront the ideas of Heidegger and the Buddha on two main axes. First, we investigate how both understand the individual's relationship with finitude. For Heidegger, anxiety reveals the finite and indeterminate nature of existence, while the Buddha describes suffering as inherent to the samsaric condition and arising from ignorance about impermanence. Second, we analyze everyday behaviors that express the escape from this reality, such as Heidegger's descriptions of idle talk, curiosity and ambiguity, in parallel with the Buddhist notions of greed, delusion, and distorted views. The objective of the study is not to rigidly equate Heidegger and the Buddha or to investigate influences between their philosophies, but rather to promote an open dialogue that illuminates the nuances of our mode of everyday being. From distinct but in some ways complementary perspectives, the two thinkers offer profound insights into how everyday life shapes and obscures our relationship with finitude and the search for meaning. This intellectual encounter seeks not only to understand these issues but also to contribute to a broader understanding of human existence, its complexities, and challenges.